The Implementation Of Agrarian Reform In Semarang Regency - Anggono, Bayu Dwi; Wahanisa, Rofi (UI Scholars Hub, 2018)
The principle of national agrarian reform (Agrarian Reform) basically refers to the 1960 Basic Agrarian Law (UUPA), especially Articles 1 to Article 15 and Article 4 of the MPR Decree No. IX of 2001. Agrarian reform is needed to restructure the control, ownership, use and utilization of agrarian resources. Agrarian Reform is tested at the local level such as Semarang regency. In this study, the statements of the problem are: (a) how is the implementation of asset reform? and (b) how do the related institutions support access reform developed in Semarang regency? The study used a descriptive-qualitative method with a sociological and juridical approach. The results showed that the implementation of asset reform in Semarang Regency was conducted through Agrarian National Operation Project (PRONA). Furthermore, the related institutions supported access reform by implementing various programs although their implementations were not optimal.